Increased TGF-β1 level after cocoa administration during orthodontics tooth movement in Cavia cobaya - Fikri, Annisa Nurul; Farmasyanti, Cendrawasih Andusyana; Pudyani, Pinandi Sri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Orthodontic tooth movement (OTM) is a process of tooth movement in the alveolar socket through a bone remodeling process. Cocoa contains caffeine as a bioactive component. The number of studies on the effects of caffeine on orthodontic tooth movement is rising. Purpose: This study aimed to determine the effect of caffeine in cocoa administration on TGF-β1 levels in the pressure side during orthodontic tooth movement. Methods: Twelve Cavia cobaya were divided into 4 groups: control group (ONC), treatment group with 2.3 mg caffeine in cocoa (OWC1), 3.45 mg dose (OWC2) and 4.6 mg dose (OWC3) (n=3). A NiTi open coil spring with light force was applied to two lower incisors tooth of Cavia cobaya. TGF-β1 level in GCF of the pressure side was analyzed using ELISA on days 0, 1, 7, and 14. Data were analyzed using the Two-way ANOVA test (p<0.05) and the LSD Post-Hoc test. Results: Research indicated improvement of TGF-β1 level from the control group with the least average followed group caffeine in cocoa 2.3 mg (OWC1), 3.45 mg (OWC2), and 4.6 mg (OWC3) (p<0.05). Conclusion: This study confirmed that caffeine in cocoa administration increase TGF-β1 level during orthodontics tooth movement on Cavia cobaya in the pressure side.